Pengembangan Video Pembelajaran Pada Materi Sistem Sirkulasi Tingkat SMA/MA - Maisal, Agung Soleh; Susanti, Diana; Fitriani, Vivi (CV. ITTC INDONESIA, 2025)
This study was conducted to produce learning media in the form of learning videos used by teachers in learning activities. Teachers use learning media in the form of videos taken from YouTube. Because teachers do not have their own learning videos designed. Videos taken from YouTube also do not support the material delivered because the content of the material from the videos taken from YouTube is not in accordance with the learning objectives, namely the video does not describe the latest material that is in accordance with the student's handbook, as a result students find it difficult to understand the contents of the videos delivered by the teacher. The use of available learning media is very limited during the learning process. The media used during learning is still infocus. Therefore, other learning resources are needed to help students understand. One effort to facilitate the learning process is by having media in the form of learning videos. The purpose of this study was to determine the development of learning media in the form of learning videos on the material of the circulatory system for SMA/MA class XI which is valid and practical. The type of research used is development research with a 4D development research model (Define, Design, Development, Disseminate). This research was carried out until the development stage, namely the validity test and practicality test. The results of the validity test showed that this learning video was in the very valid criteria with a validity value of 91%. The results of the practicality test by the teacher showed a value of 81% with practical criteria and the results of the practicality test of the learning video by students showed a value of 86% with very practical criteria. It can be concluded that the learning video on the material of the circulatory system for the SMA/MA level that was developed is valid and practical.